2007
DOI: 10.1089/cpb.2006.9993
|View full text |Cite
|
Sign up to set email alerts
|

Affective Interactions Using Virtual Reality: The Link between Presence and Emotions

Abstract: Many studies showed the ability of movies and imagery techniques to elicit emotions. Nevertheless, it is less clear how to manipulate the content of interactive media to induce specific emotional responses. In particular, this is true for the emerging medium virtual reality (VR), whose main feature is the ability to induce a feeling of "presence" in the computer-generated world experienced by the user. The main goal of this study was to analyze the possible use of VR as an affective medium. Within this general… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

37
514
3
11

Year Published

2010
2010
2024
2024

Publication Types

Select...
4
2
1

Relationship

0
7

Authors

Journals

citations
Cited by 882 publications
(565 citation statements)
references
References 18 publications
37
514
3
11
Order By: Relevance
“…Previous findings have shown a correlation between emotions and presence (Riva et al, 2007;Robillard et al, 2003) and a bidirectional relationship between these constructs Michaud et al, 2004;Riva et al, 2007). Riva et al (2007) showed that positive and negative mood could be efficiently induced by immersions in carefully designed virtual environments.…”
Section: Discussionmentioning
confidence: 93%
See 3 more Smart Citations
“…Previous findings have shown a correlation between emotions and presence (Riva et al, 2007;Robillard et al, 2003) and a bidirectional relationship between these constructs Michaud et al, 2004;Riva et al, 2007). Riva et al (2007) showed that positive and negative mood could be efficiently induced by immersions in carefully designed virtual environments.…”
Section: Discussionmentioning
confidence: 93%
“…Visiting a mythological Egyptian temple may represent a positive experience for most participants in the sample. It is important to point out however that virtual environments used by other researchers to induce positive mood (Banos et al, 2004;Riva et al, 2007) were especially designed to have a strong positive valence. No such efforts were invested in the current environment and, therefore, it was not expected to have such a soothing effect.…”
Section: Discussion For Experimentsmentioning
confidence: 99%
See 2 more Smart Citations
“…Presence has been found to be strongly related to the capability of a mediated environment -including 3DTV, videogames and artistic and cultural heritage virtual environments (VEs) -to elicit emotions [61,90] and, in particular, enjoyment [73,85]. In consequence, an enhanced sense of Presence is considered to have a direct impact on the adoption potential of these applications.…”
Section: The Media Experience: Presence Emotions and Quality Judgmentmentioning
confidence: 99%